한국 내 베트남 이민여성의 성지식과 태도간의 관계 - Nguyen Ho Phuong Nga (The Graduate School, Ajou University, 2011)
Sexuality is one of the vital factors which strongly affect the individual well-being and quality of life. The aim of this study was to assess the relationship between knowledge and attitude toward sexuality of Vietnamese immigrant women in Korea. A cross-sectional survey using a sample of 135 Vietnamese immigrant women was conducted in Gyeonggi province, South Korea. A self-reported questionnaire concerning knowledge and attitude toward sexuality was used for data collection. Statistical package for the social sciences (SPSS) version 17 was used for the data analysis of the study. The result demonstrated a level of knowledge toward sexuality with a mean score of 13.21 ± 5.22 and attitude toward sexuality with a mean score of 42.42 ± 6.43 among subjects. A positive relation between knowledge and attitude toward sexuality was also found in this study (r = 0.19, p = .032). There were significant differences in level of knowledge toward sexuality relating to education (F (3, 131) = 9.55, p < .001) and family income (F (2, 132) = 4.20, p = .017). Moreover, a significant difference in attitude toward sexuality was noted on living period in Korea (F (2, 132) = 4.95, p = .008). In conclusion, this study indicated the need for sexual education program to improve the knowledge about sexuality as well as to create the more positive attitude toward sexuality among Vietnamese immigrant women in South Korea.
학위논문(석사)--아주대학교 일반대학원 :간호학과,2011. 2
Keywords: KNOWLEDGE AND ATTITUDE TOWARD SEXUALITY